Inhibitory effect of potassium channel openers on proliferation of cultured rabbit aortic smooth muscle cells - Shi Dao-Hua; Guo Zhao-Gui (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of pinacidil (Pin), nicorandil (Nic), RP 49356 (RP), and lemakalim (Lem) on phenylephrine (PE)-induced proliferation of cultured rabbit aortic smooth muscle cells (ASMC). METHODS: The [3H]thymidine incorporation into DNA and number of ASMC were measured. RESULTS: [3H]Thymidine uptake induced by PE was markedly inhibited by Pin, Nic, RP, and Lem (0.1-10 mumol.L-1). Only RP inhibited [3H]thymidine uptake without PE-pretreatment. Cell growth induced by PE was completely inhibited by Pin. CONCLUSION: Pin, Nic, RP, and Lem showed potent antiproliferation of ASMC.